2015
DOI: 10.1111/sjop.12222
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of the Interactive Test of Interpersonal Behavior (ITIB): a pilot study examining interpersonal deficits in chronic depression

Abstract: Chronic depression is assumed to be caused and maintained by interpersonal deficits. We describe the development and psychometric evaluation of the Interactive Test of Interpersonal Behavior (ITIB) that we developed for self-assessment of these deficits. Participants with chronic depression (CD, N = 15), episodic depression (ED, N = 15) and healthy controls (HC, N = 15) participated in this pilot study. They completed the ITIB and a number of pen and paper questionnaires including the Lübeck Questionnaire of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
5
0
3
Order By: Relevance
“…The differences in level of preoperational thinking at baseline for the groups PD and ED are consistent with other studies (18,19). We did find a significant group difference, with the group PD showing higher levels of preoperational thinking than the other groups, whereas the group of ED showed significant higher levels of preoperational thinking in comparison to the group HC.…”
Section: Comparison To Existing Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…The differences in level of preoperational thinking at baseline for the groups PD and ED are consistent with other studies (18,19). We did find a significant group difference, with the group PD showing higher levels of preoperational thinking than the other groups, whereas the group of ED showed significant higher levels of preoperational thinking in comparison to the group HC.…”
Section: Comparison To Existing Studiessupporting
confidence: 91%
“…Our study aims to provide a more detailed view of social cognition by using a measure developed specifically for preoperational thinking and examining its association with the long-term course of depressive symptoms both in patients and healthy controls. Previous studies using this measure have shown higher levels of preoperational thinking in patients with PD compared to patients with ED or healthy controls ( 11 , 18 , 19 ). Preoperational thinking was also linked to childhood maltreatment with a mediating effect of interpersonal fears ( 11 ), as well as mediating the association of childhood maltreatment and a hostile interpersonal style ( 20 ).…”
Section: Introductionmentioning
confidence: 91%
“…Another shortcoming of the current study is that interpersonal problems were assessed only by one self‐report. The "interactive test of interpersonal behavior” (ITIB; Klein et al, 2016) or the “impact message inventory” (IMI; Kiesler & Schmidt, 2006), for example, could provide valuable complementary information. The ITIB is a self‐assessment instrument in which patients have to give answers to specific interpersonal dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also successfully employed this interview (e.g. [31, 32]). Participants were diagnosed with PDD when meeting DSM-5 criteria for a pure dysthymic syndrome, for a persistent major depressive episode, for persistent depressive disorder with intermittent major depressive episodes, with current episode as well as without current episode.…”
Section: Methodsmentioning
confidence: 99%